(untitled) - Cheeseman, Henry R (Upper Saddle River, N.J, 2007)
The Legal Environment of Business and Online Commerce, 6e examines how the current legal environment, government regulation, and e-commerce environment impact today's business decisions.
Keywords: Business law,Luật thương mại; United States,Hoa Kỳ